Genomic and Epidemiological Investigations Reveal Chromosomal Integration of the Acipenserid Herpesvirus 3 Genome in Lake Sturgeon Acipenser fulvescens - Sharon Clouthier; Umberto Rosani; Arfa Khan; Qiuwen Ding; Eveline Emmenegger; Zhuozhi Wang; Thomas Nalpathamkalam; Bhooma Thiruvahindrapuram (Viruses)
DNA sequence from a new alloherpesvirus named acipenserid herpesvirus 3 (AciHV-3) was found in sturgeon species that are vulnerable to decline globally. A study was undertaken to develop a better understanding of the virus genome and to develop diagnostic tools to support an epidemiological investigation. A 184,426 bp genome was assembled from PacBio HiFi sequences generated with DNA from a Lake Sturgeon Acipenser fulvescens gonad cell line. The AciHV-3 genome was contiguous with host chromosomal DNA and was structured with telomere-like terminal direct repeat regions, five internal direct repeat regions and a U region that included intact open reading frames encoding alloherpesvirus core proteins. Diagnostic testing conducted with a newly developed and analytically validated qPCR assay established the ubiquitous presence and high titer of AciHV-3 DNA in somatic and germline tissues from wild Lake Sturgeon in the Hudson Bay drainage basin. Phylogenetic reconstructions confirm that the monophyletic AciHV-3 lineage shares a common ancestor with AciHV-1 and that AciHV-3 taxa cluster according to their sturgeon host. The same genotype of AciHV-3 is found in disjunctive Lake Sturgeon populations within and among drainage basins. The results support the hypotheses that AciHV-3 has established latency through germline chromosomal integration, is vertically transmitted via a Mendelian pattern of inheritance, is evolving in a manner consistent with a replication competent virus and has co-evolved with its host reaching genetic fixation in Lake Sturgeon populations in central Canada.